Implementation of the Healthy School Program in Junior High School - Rr Mini Sariwulan (STAI Hubbulwathan Duri, 2023)
A healthy school is a school that has a living environment that reflects a healthy life, so as to ensure that the learning process takes place properly and creates conditions that support the achievement of students' ability to live a healthy life. This study aims to determine how to implement a healthy school program in a junior high school in Unggul Sekayu. Informants in this study were seven people consisting of school principals, teachers, employees, and students. Data was collected through observation, interviews and documentation. Meanwhile, data analysis uses data reduction, presentation, and conclusion drawing. This research shows that the healthy school program at junior high school in Unggul Sekayu runs according to the SKB 4 Ministerial regulations and has a vision, mission, benefits, goals, and opportunities. The healthy school program is supported by human resources such as principals and vice principals, students, teachers, staff, P2M, UKS team, infrastructure and curriculum. In the process, it uses the